Stratigraphy and chronology of Pleistocene coastal deposits in northern Aquitaine, France: a reinvestigation = Révision stratigraphique et chronologique de la séquence Pléistocène du littoral Nord-aquitain - Bosq, Mathieu; Bertran, Pascal; Beauval, Cédric; Kreutzer, Sebastian; Duval, Mathieu; Bartz, Melanie; Mercier, Norbert; Sitzia, Luca; Stephan, Pierre (Quaternaire, 2019)
Pleistocene deposits exposed along the coast of the Médoc area, south‑west France, represent valuable palaeoenvironmental archives that have been the subject of extensive work in the past few decades. To further understand the palaeoenvironmental history and sedimentary dynamics of these deposits, a detailed lithostratigraphic study was performed on a series of new sections. Additionally, new chronological data were obtained from the combination of luminescence (OSL, IR-RF) and electron spin resonance (ESR) dating of quartz and feldspar grains (Kreutzer et al., 2018). The investigated sections comprise estuarine, lacustrine and peaty deposits (Négade Formation, Argiles du Gurp Formation), aeolian sands (Sables du Gurp Formation) and colluvial units (Grès de l’Amélie Formation). The Argiles du Gurp Formation, in which many remains of Palaeoloxodon antiquus were found, support the hypothesis of a progressive replacement of a tide-influenced marsh by a peaty fresh-water pond during the Holsteinian Interglacial (MIS 11). IR-RF dating of green estuarine clays at L’Amélie, in the northernmost part of the investigated area, strongly suggests that they do not belong to the Argile du Gurp Formation, but were deposited during the MIS 9 sea level highstand. The estuarine deposits are overlain by sandsheets (Sables du Gurp Formation) dated to MIS 10 and MIS 8 at Pointe de la Négade in the southern part of the study area, and to MIS 8 at L’Amélie. Syngenetic frost cracks testify to a periglacial depositional environment. Regional studies show that the Sables du Gurp Formation is a local equivalent of the Sables des Landes Formation, and corresponds to the oldest aeolian phase recorded in south-west France so far. Colluvial material (Grès de l’Amélie Formation) dated to the Weichselian pleniglacial (MIS 2) fill small palaeo-valleys incised in the Sables du Gurp Formation. Holocene coastal dunes cover the whole sequence.
Gesehen am 31.03.2025